Productivity and nutritional value of 20 species of perennial legumes in a low‐rainfall Mediterranean‐type environment in southern Australia. (25th March 2021) - Norman, Hayley C.; Humphries, Alan W.; Hulm, Elizabeth; Young, Paul; Hughes, Steve J.; Rowe, Trevor; Peck, David M.; Vercoe, Phil E.
Abstract: In the rain‐fed mixed‐farming systems of southern Australia, the consistent supply of high‐value forage is limited by a range of climatic, edaphic and systems constraints. Over 2 years, we compared biomass production and nutritional value of 30 accessions of perennial legumes, and predicted intake, grazing days and growth of ewes and lambs. There was significant variation in nutritional value and biomass production between and within species. Lucerne ( Medicago sativa ) and sulla ( Hedysarum coronarium ) produced the greatest amount of biomass and energy. There was variability among accessions in digestibility (DMD), acid detergent fibre (ADF) and crude protein, and the rate of change in these traits as plants matured. Trifolium species had the highest DMD across all growth stages. Hairy canary clover ( Dorycnium hirsutum ), erect canary clover ( Dorycnium rectum ), greater birdsfoot trefoil ( Lotus uliginosus ), Australian trefoil ( Lotus australis ) and running postman ( Kennedia prostrata ) had energy levels that would not maintain liveweight of mature sheep. In the second year, species differed in response to harvesting treatments. Lucerne and sainfoin ( Onobrychis viciifolia ) were more productive under a frequent cutting regime. Accessions of white clover ( Trifolium repens ), red clover ( Trifolium pratense ), alsike clover ( Trifolium hybridum ), cullen ( Cullen australasicum ), strawberry clover ( Trifolium fragiferum ), sainfoin and birdsfoot trefoil ( Lotus corniculatus ) showed some promise, while Tedera ( Bituminaria bituminosa ) and milkvetch ( Astragalus cicer ) performed poorly under the experimental conditions. We conclude by discussing additional agronomic and nutritional factors that need consideration when developing novel perennial legumes for mixed‐farming systems in the context of a changing climate.